2018
DOI: 10.18632/oncotarget.25953
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling protein HELLS is upregulated by inactivation of the RB-E2F pathway and is nonessential for osteosarcoma tumorigenesis

Abstract: Osteosarcoma is the most common primary bone malignancy in children and adolescents. Among the various molecular mechanisms implicated in osteosarcomagenesis, the RB-E2F pathway is of particular importance as virtually all cases of osteosarcoma display alterations in the RB-E2F pathway. In this study, we examined the transcription factor E2F family members that are associated with increased malignancy in Rb1-null osteosarcoma tumors. Using genetically engineered mouse models of osteosarcoma, we found that loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…DNA methylation is catalyzed by enzymes in the DNA methyltransferase family (DNMTs), including DNMT1, which is associated with the maintenance of DNA methylation [ 82 , 83 ], and DNMT3A and DNMT3B, which are responsible for de novo DNA methylation [ 84 ]. pRB not only transcriptionally represses the expression of DNMT1 and DNMT3A / B [ 85 , 86 , 87 ], but also physically interacts with DNMT1 and chromatin remodelers that can recruit DNMT1 and DNMT3A/B to affect DNA methylation [ 88 , 89 , 90 , 91 ].…”
Section: Prb In Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is catalyzed by enzymes in the DNA methyltransferase family (DNMTs), including DNMT1, which is associated with the maintenance of DNA methylation [ 82 , 83 ], and DNMT3A and DNMT3B, which are responsible for de novo DNA methylation [ 84 ]. pRB not only transcriptionally represses the expression of DNMT1 and DNMT3A / B [ 85 , 86 , 87 ], but also physically interacts with DNMT1 and chromatin remodelers that can recruit DNMT1 and DNMT3A/B to affect DNA methylation [ 88 , 89 , 90 , 91 ].…”
Section: Prb In Dna Methylationmentioning
confidence: 99%
“…Unpublished studies from our lab using genetic engineered mouse models of retinoblastoma also indicate that UHRF1 overexpression is required for the epigenetic changes that drive retinoblastoma tumor progression and in the absence of UHRF1, retinoblastoma tumors fail to form. HELLS is also transcriptionally regulated by the pRB/E2F pathway and overexpressed in multiple types of cancer, including retinoblastoma [ 90 , 96 , 97 ]. HELLS remodels chromatin to render DNA accessible to DNMT3 to support de novo DNA methylation and stable gene silencing during cellular differentiation.…”
Section: Prb In Dna Methylationmentioning
confidence: 99%
“…Previous studies have shown that HELLS is regulated through the RB/E2F pathway and that loss of RB1 results in upregulation and overexpression of HELLS, a process that may contribute to epigenetic changes that drive tumor progression 7,8,10 . We verified that HELLS overexpression occurs soon after tumor initiation in Chx10-Cre Rb1 lox/lox p107 −/− (Rb1/p107 DKO; Fig.…”
Section: Hells Is Transcriptionally Repressed By the Rb Familymentioning
confidence: 99%
“…Other groups and we have identified HELLS as a transcriptional downstream target gene of E2F1 that is overexpressed in cancer and contributes to tumor progression 9,10,30 . The evidence of direct regulation of HELLS by the RB family was limited to in vitro studies in gliomas and osteosarcoma 7,9 . In this study, we confirmed that the RB/E2F signaling pathway directly regulates transcriptional activation of HELLS in the developing retinae.…”
Section: Hells Is Downregulated By Rb and P107 During Late Retinal DImentioning
confidence: 99%
See 1 more Smart Citation